Specification for ground investigation (Site investigation in construction, 1993)
This Specification includes associated Schedules and a Bill of Quantities, and is intended for general application to ground investigation work. The Bill of Quantities is presented as a preamble and a comprehensive list of work items, which conveniently cross-relate to the Specification items.